Voltage-mode control of boost converters - Chan, Chun Kit. (2013)
In this project, the investigation of voltage-mode control of boost converters is presented. Both the elementary boost converter and the two-stage boost converter are addressed. Two different voltage mode feedback controllers are used for controlling the output voltage of these boost converters. The report describes the implementation of these boost converters and the corresponding voltage-mode controllers. Experimental results are also presented to show the features and effectiveness of the voltage-mode controllers under different operating conditions